EFEKTIVITAS TEACHY APP DALAM MENINGKATKAN KETERAMPILAN ARGUMENTASI SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA: One Group Pretest–Posttest - Permana, Haikal; Camellia, Camellia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological developments require educators to utilize digital media that can support 21st-century skills, especially critical thinking skills. This study aims to determine the effectiveness of the Teachy App in improving students' critical thinking and argumentation skills. The method used is a One Group Pretest–Posttest design with a quantitative approach. Students were given a pretest, received treatment through the use of the Teachy App, and then underwent a posttest. Data analysis used the N-Gain and Wilcoxon tests. The results showed an average N-Gain value of 0.64 (moderate category), and a Wilcoxon significance value of 0.00 <0.05, indicating a significant increase after treatment. Thus, the Teachy App is proven effective as an interactive learning medium that improves students' critical thinking and argumentation skills and is relevant to support 21st-century competencies.